Exploring atherosclerosis imaging with contrast-enhanced MRI using PEGylated ultrasmall iron oxide nanoparticles - Zhang, Ruru; Lu, Kuan; Xiao, Li; Hu, Xuelan; Cai, Wu; Liu, Linjiang; Liu, Yan; Li, Weihua; Zhou, Hui; Qian, Zhiyuan; Wang, Sixia; Chen, Can; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Plaque rupture is a critical concern due to its potential for severe outcomes such as cerebral infarction and myocardial infarction, underscoring the urgency of noninvasive early diagnosis. Magnetic resonance imaging (MRI) has gained prominence in plaque imaging, leveraging its noninvasiveness, high spatial resolution, and lack of ionizing radiation. Ultrasmall iron oxides, when modified with polyethylene glycol, exhibit prolonged blood circulation and passive targeting toward plaque sites, rendering them conducive for MRI. In this study, we synthesized ultrasmall iron oxide nanoparticles of approximately 3 nm via high-temperature thermal decomposition. Subsequent surface modification facilitated the creation of a dual-modality magnetic resonance/fluorescence probe. Upon intravenous administration of the probes, MRI assessment of atherosclerotic plaques and diagnostic evaluation were conducted. The application of Flash-3D sequence imaging revealed vascular constriction at lesion sites, accompanied by a gradual signal amplification postprobe injection. T1weighted imaging of the carotid artery unveiled a progressive signal ratio increase between plaques and controls within 72 h post-administration. Fluorescence imaging of isolated carotid arteries exhibited incremental lesion-to-control signal ratios. Additionally, T1 imaging of the aorta demonstrated an evolving signal enhancement over 48 h. Therefore, the ultrasmall iron oxide nanoparticles hold immense promise for early and noninvasive diagnosis of plaques, providing an avenue for dynamic evaluation over an extended time frame.